Influência da saturação de fundo e do carregamento orgânico no desempenho de wetland vertical aplicado ao tratamento de esgoto doméstico bruto - Marchioro, Luis Gustavo (2020)
The vertical flow constructed wetlands (VFCW) are natural and low cost systems and that present relative operational simplicity, making this technology attractive to the treatment of effluents in a decentralized way, fitting well to the needs of small communities. These systems have a good removal of carbonaceous organic matter and significant nitrification. However, total nitrogen removal is limited in these systems. An alternative to this limitation is the saturation of a layer of the filtering bed aiming the formation of an anoxic environment seeking to make the denitrification process more efficient. The objective of this study was to evaluate the performance of pilot scale systems of traditional VFCW and adapted systems with a saturated bottom in a treatment of raw domestic wastewater. The experiment was operated for 339 days, monitored for 218 days and consisted of using PVC columns with 0,031 m² of surface area, filled with gravel, transplanted with Canna sp., fed 5 times a day, for 3,5 days a week with the same time destined to rest (without feeding). The performance of the columns was assessed for three hydraulic loading rates - HLR (40, 70 and 100 mm d-¹) with the respective average organic loads of 49, 86 e 123 g DQO m-² d-¹ in two conditions: free drainage (DL) and saturated bottom (FS). The saturation layer corresponds to 1/3 of the bed (25cm/75cm), resulting in six evaluated columns, which were named as DL1 and FS1 (40 mm d-¹), DL2 and FS2 (70 mm d-¹) and DL3 and FS3 (100 mm d-¹). There was a better performance in COD removal for columns with saturated bottom (96, 95 e 93 % for FS1, FS2 and FS3, respectively), compared to free drainage columns (86, 84 and 78 % for DL1, DL2 and DL3, respectively). Better performance in the removal of TN was also observed in the FS columns (94, 87 and 79% for FS1, FS2 and FS3, respectively), compared to the DL columns (80, 73 and 63 % for DL1, DL2 and DL3, respectively). Increasing the HLR, a limitation was observed for the saturated bottom columns in the removal of N-NH4 +, with FS3 presenting a performance lower than DL3 for this parameter. The increase of HLR showed to influence the accumulation of solid material on the surface and the development of vegetation. At the end of the operation period, the columns had an average accumulation of sludge on the surface of 0.128, 0.272 and 0,477 kg m-² for pairs DL1/FS1, DL2/FS2 and DL3/FS3, respectively, as well an average production of vegetable biomass of 1.70, 2.78 and 4.74 kg m-². With the realization of this experiment, we can conclude that the adaptation of bottom saturation layer plays an important role in the operation of VFCW, being able to substantially increase the performance of these systems when applied to the treatment of raw domestic sewage.